Correlations between water absorption, electrical resistivity and compressive strength of concrete with different contents of pozzolan - Medeiros-Junior, Ronaldo Alves de; Munhoz, Guilherme da Silva; Medeiros, Marcelo Henrique Farias de (Revista ALCONPAT, 2019)
This research confronts the following concrete properties: water absorptions (by immersion and capillarity), electrical resistivity and compressive strength. Concrete mixtures with two types of cement were tested. Results showed that concretes with higher content of pozzolan had higher resistivity and greater absorption by capillarity, for water/cement ratios lower than 0,60. This behavior is attributed to reduced pore diameters and microstructure densification. However, for water/cement ratio of 0,60, concrete with lower content of pozzolan presented higher absorption by capillarity. It was observed that the compressive strength and the electrical resistivity behaved inversely proportional to the water/cement ratio, and the absorption by immersion and capillarity are directly proportional to the water/cement ratio. Correlations with high determination coefficients were found between tests.